Penerapan Machine Learning Untuk Mengategorikan Sampah Plastik Rumah Tangga - Hendri, Hendri; Hoki, Leony; Agusman, Veirry; Aryanto, Didik (STMIK TIME, 2021)
Plastic waste is the result of human needs for plastic-based products. Due to high needs, the manufacture and use of plastics as raw materials produced do not use plastics as raw materials for their manufacture. Side effects of this phenomenon cause plastic waste to be transferred to the Final Shelter (TPA). Plastic waste is divided into 7 types, some can be replaced, recycled, and reused. To be able to do better sorting and screening of plastic waste, human labor is needed. This causes humans to have the ability to sort and filter visual objects, but humans are less consistent in various influencing factors. However, if this is applied to a computing system, the plastic waste treatment system will provide consistent results. If this system is applied in various layers of waste treatment, the plastic waste that pollutes the environment will be reduced. With the help of Machine Learning and Deep Learning,we can apply human visual abilities to computer systems.